Psychological and pedagogical conditions of activity and the main directions of the virtual laboratory - Исалиева, Сауле; Абаева, Галия; Жанкушков, Бауыржан; Рашидинов, Дамир (Pedagogy and Psychology, 2022)
The article deals with the psychological and pedagogical congitions of the virtual laboratory of the social and humanitarian direction. The authors attempted to analyze existing digital platforms and resources, various approaches to understanding the virtual laboratory, its methodological support, organization of consulting assistance and tutor support for users, independent and group work of students, etc. In their study, they relied on one of the main tasks – the theoretical justification and development of a structural model of a psychological and pedagogical virtual laboratory with further practical testing and implementation. It is known that psychological and pedagogical conditions are one of the types of pedagogical conditions, which in the general sense means the process of personality development, in the narrow sense – the totality of external circumstances with the internal unity of phenomena. This research is carried out within the framework of the project “Designing a virtual laboratory within the framework of a developing educational environment” and is funded by the Abai University (contract No. 3 dated 11 February, 2022).